Urban sustainability: from neoliberal governance to the right to the city. (2016) - Elliott, Brian
The sustainable development (SD) paradigm has attained a near universal level of acceptance among environmental theorists and practitioners. Part of the success of SD over the last three decades rests on its assumed political neutrality. This paper contests that neutrality and argues that in fact SD is a clear outshoot of neoliberal governance. The idea of the right to the city offers a concrete counter-model to SD as it relates specifically to the city. Finally, the most salient environmental failure of SD concerns intergovernmental efforts to tackle climate change. On this front, the widely touted mechanism of metropolitan climate action plans merely serves to undermine further the credibility of the nation state as an environmental agent. As Anthony Giddens (2011) has recently argued, it is necessary to overcome the neoliberal limits placed on state action if credible long-term responses to climate change are to emerge.